The Implementation of Human Resource Management (HRM) in Village Government - Diyanto, Chafid; Linda, Ade; Naimatul Khanafiah, Aulia; Febriani, Dena; Ramadhan, Nizar (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study analyzes the implementation of Human Resource Management in the Purbadana Village Government, Kembaran District, Banyumas Regency. Focusing on five key aspects—planning, recruitment, selection, training and development, and performance assessment, the research employs a qualitative approach with data collected from 10 HR participants within the village government. The findings reveal that the Purbadana Village Government has effectively applied HR management principles, leading to enhanced performance of village officials, improved administrative efficiency, and more responsive and transparent public services. Key success factors include strong leadership, officials’ commitment, integrity, and adequate infrastructure support. However, challenges persist, particularly in addressing residents’ aspirations and complaints related to the distribution of Village Fund Assistance (Bantuan Dana Desa). To address these gaps, strengthening communication capacity and problem-solving skills is essential for future improvements. The study’s outcomes provide valuable insights for enhancing village governance and sustainable HR development at the local level.